Bioactivity of Pyrrolo[1,2-a]pyrazine-1,4-dione,hexahydro-3-(phenylmethyl)- Extracted from Streptomyces sp. VITPK9 Isolated from the Salt Spring Habitat of Manipur, India - Kannabiran, Dr. Krishnan (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of the present study was to evaluate the biological activity of pyrrolo[1,2-a]pyrazine-1,4-dione,hexahydro-3-(phenylmethyl)- (PPDHP) extracted from Streptomyces sp. VITPK9, isolated from the brine spring of Thoubal district, Manipur, India. Materials and Methods: Hemolytic effect of the lead compound was determined, and human erythrocytes (red blood cells) were collected and used within 24 h. For genotoxicity study, chromosome preparations were obtained from phytohemagglutinin-stimulated peripheral blood lymphocytes. The viability of cells was evaluated by 3-(4,5-dimethythiazol-.2-yl)-2,5-diphenyl tetrazolium bromide assay on RAW 264.7 cell lines. Results and Discussion: The antifungal compound PPDHP showed mild hemolytic activity with effective concentration 50% value of 115.5 Î¼g/mL on human erythrocytes. Cytotoxicity study on normal cell-line RAW 264 exhibited a moderate toxicity with 50% inhibitory concentration value of 500 Î¼g/mL. Genotoxicity study revealed that the compound showed minimal chromosomal aberrations when compared to streptomycin. Conclusion: The results of the study suggest that the diketopiperazine type of compounds extracted from Streptomyces sp. VITPK9 can be used as the potential antifungal compound.